2021
DOI: 10.3390/jmse9101121
|View full text |Cite
|
Sign up to set email alerts
|

Non-Indigenous Species on Artificial Coastal Environments: Experimental Comparison between Aquaculture Farms and Recreational Marinas

Abstract: Globally, there is growing concern regarding the effects of the increasing anthropogenic pressures in marine communities. Artificial structures such as marinas and aquaculture facilities serve as invasion hotspots; hence, monitoring fouling communities on these structures can be valuable for detecting new invasions. In the current study, 24 settlement PVC plates were deployed for three months to compare the recruitment ability of these two artificial environments along the south coast of the offshore island of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 71 publications
(91 reference statements)
0
9
0
Order By: Relevance
“…Some organisms colonize surfaces forming biofouling communities that change over time, while others are benthic (living on the sea floor), or possess larval stages that inhabit temporarily the water column and may be mostly found in zooplankton, depending on the sampled season (Vinagre et al 2020). In addition, and due to the presence of many artificial substrates (e.g., floating pontoons, cables, boats, buoys) and higher availability of nutrients, recreational marinas are highly prone to be colonized by biofouling communities (e.g., mussel lines) which per se can also constitute an augmented surface of potential niches available for NIS settlement (Png-Gonzalez et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some organisms colonize surfaces forming biofouling communities that change over time, while others are benthic (living on the sea floor), or possess larval stages that inhabit temporarily the water column and may be mostly found in zooplankton, depending on the sampled season (Vinagre et al 2020). In addition, and due to the presence of many artificial substrates (e.g., floating pontoons, cables, boats, buoys) and higher availability of nutrients, recreational marinas are highly prone to be colonized by biofouling communities (e.g., mussel lines) which per se can also constitute an augmented surface of potential niches available for NIS settlement (Png-Gonzalez et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is also important when monitoring non-indigenous invertebrate species as organisms introduced by hull fouling can pass to the hard artificial substrates of the marinas and harbours, through hull cleaning operations; or from the water column through larval stages or propagules (European Environment Agency 2021). Recent studies have shown that recreational marinas are more relevant for the spreading of NIS than it was supposed, as they present communities that diverge from those recovered in the nearest harbours, and some even present a higher number of NIS, or different NIS than those detected in the harbours (Ferrario et al 2017; Chebaane et al 2019; Afonso et al 2020; Png-Gonzalez et al 2021). This suggests that recreational vessels, and not only larger industrial vessels, are very relevant vectors for NIS spreading (Ferrario et al 2017; Chebaane et al 2019; Afonso et al 2020; Png-Gonzalez et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identified fouling species were classified by major taxa, morphology (encrusting, massive and arborescent) and status (native, cryptogenic and NIS). Species status was assigned based on the existing literature [44,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Data Acquisition and Treatmentmentioning
confidence: 99%
“…Indeed, hull fouling is the most significant vector of the introduction of marine NIS in the Madeira Archipelago coastal waters (Canning-Clode et al 2013a ; Ramalhosa et al 2014 , 2017a , 2017b , 2019 ; Ramalhosa and Canning-Clode 2015 ; Souto et al 2018 ). Moreover, offshore aquaculture activities facilitate the local dispersion of NIS (Nunes et al 2014 ; Campbell et al 2017 ), posing a serious environmental threat to biodiversity and ecosystem function (Mack et al 2000 ; Png-Gonzalez et al 2021 ). Aquaculture artificial substrates may serve as stepping stones, offering novel niches for opportunistic colonizers, including NIS, favoring their dispersal (De Mesel et al 2015 ) and supplying substrate to establish other NIS (Rius et al 2011 ; Png-Gonzalez et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%